Neuropathy in a patient with lymphocytic thrombophilic arteritis. (6th January 2012) - Shen, Sarah; Williams, Richard A; Kelly, Robert I
ABSTRACT A 35‐year‐old Lebanese woman presented with a 3‐year history of persistent, localized livedo racemosa over her feet, distal legs and forearms that was associated with the development of lower limb sensorimotor neuropathy. Investigations revealed the patient was heterozygous for prothrombin gene mutation and was also found to have a T‐cell receptor gamma chain gene rearrangement. Histological examination revealed a mid‐lower dermal medium vessel lymphocytic vasculitis with prominent fibrinoid ring within its wall. These findings are consistent with a recently described condition known as lymphocytic thrombophilic arteritis. This has so far been considered to be a benign clinical condition not associated with extra cutaneous manifestations. The novel findings in the present case are the associated sensorimotor neuropathy and the characteristic fibrin ring appears to be intramural rather intraluminal in location. The findings of a T cell gene rearrangement and a prothombin gene mutation suggest that both immunological and thrombophilic factors might contribute to the development of this condition.